2019
DOI: 10.1136/bmjopen-2018-024995
|View full text |Cite
|
Sign up to set email alerts
|

How does priority setting for resource allocation happen in commissioning dental services in a nationally led, regionally delivered system: a qualitative study using semistructured interviews with NHS England dental commissioners

Abstract: ObjectivesTo understand approaches to priority setting for healthcare service resource allocation at an operational level in a nationally commissioned but regionally delivered service.DesignQualitative study using semistructured interviews and a Framework analysis.SettingNational Health Service dentistry commissioning teams within subregional offices in England.ParticipantsAll 31 individuals holding the relevant role (dental lead commissioner in subregional offices) were approached directly and from this 14 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The 25 papers that met the inclusion criteria and were subject to data extraction provide relevant information from ten countries: Australia [ 19 – 21 ]; Austria [ 22 ]; Canada [ 23 27 ]; Israel [ 28 ]; Korea [ 29 , 30 ]; New Zealand [ 31 ]; Norway [ 32 ]; Sweden [ 33 , 34 ]; UK [ 35 42 ]; US [ 43 ]. The list of frameworks identified in our view provides a reasonable summary of PSRA frameworks developed and implemented in health care systems in high-income countries.…”
Section: Resultsmentioning
confidence: 99%
“…The 25 papers that met the inclusion criteria and were subject to data extraction provide relevant information from ten countries: Australia [ 19 – 21 ]; Austria [ 22 ]; Canada [ 23 27 ]; Israel [ 28 ]; Korea [ 29 , 30 ]; New Zealand [ 31 ]; Norway [ 32 ]; Sweden [ 33 , 34 ]; UK [ 35 42 ]; US [ 43 ]. The list of frameworks identified in our view provides a reasonable summary of PSRA frameworks developed and implemented in health care systems in high-income countries.…”
Section: Resultsmentioning
confidence: 99%
“…Linking participants' answers with the first part on conceptualizing 'essential' in OH, the OH system, and therefore the decision-making process for coverage, should be transparent. There are robust priority setting tools available which take a multi-criteria decision analysis approach that would be useful for the OH context, specifically for the definition of a benefits basket (Listl et al, 2022;Vernazza et al, 2019Vernazza et al, , 2023). Yet, benefits baskets in OH often lacked clarity and the criteria that led to these choices were not always known (Manski et al, 2017;Vernazza et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…There are robust priority setting tools available which take a multi-criteria decision analysis approach that would be useful for the OH context, specifically for the definition of a benefits basket (Listl et al, 2022;Vernazza et al, 2019Vernazza et al, , 2023). Yet, benefits baskets in OH often lacked clarity and the criteria that led to these choices were not always known (Manski et al, 2017;Vernazza et al, 2019). The steps identified in this study can inform the different stages of a public policy process.…”
Section: Discussionmentioning
confidence: 99%
“…A series of program components for consideration for new investment, considerations for disinvestment, and program components that could be delivered more efficiently was agreed on in 2 stages. First, a long list was created from individual interviews with dental lead commissioners (methods reported elsewhere; Vernazza et al 2019 ); a meeting with the national dental team, regional commissioners, and their clinical advisers; and in PBMA panel discussions. The second stage involved the panel voting on the long-listed program components to create a shortlist for onward consideration in the “marginal analysis” part of the PBMA process.…”
Section: Methodsmentioning
confidence: 99%
“…In England, the NHS directly engages in a contract with independent dental providers ( Steele 2009 ). Previous work has shown that there is little explicit resource allocation decision making in dentistry in England ( Vernazza et al 2019 ). To the authors’ knowledge, only 1 PBMA has been undertaken in dentistry and was limited to 1 region of England ( Holmes et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%